Accuracy of heart girth tapes in the estimation of weights of pre‐weaned calves. Issue 1 (7th August 2021) - Sherwin, Virginia; Hyde, Robert; Green, Martin; Remnant, John; Payne, Emily; Down, Peter
Abstract: Background: Heart girth tapes (HGTs) are often used as an alternative to weight scales for calves. This study investigated the accuracy of HGT in estimating bodyweight and daily liveweight gain (DWLG) of pre‐weaned calves, and the impact of inter‐observer variation. Method: In Study 1, 119 calves were weighed using HGT and electronic scales on multiple occasions. Mixed‐effects models for both bodyweight and DLWG were used to determine the accuracy of HGT compared to the electronic scales. Simulation data were used to further analyse the accuracy of DLWG estimation including for factors such as the effect of group size on group DLWG estimates. In Study 2, 10 observers weighed 20 pre‐weaned calves, using HGT and electronic scales. Mixed‐effect model was used to investigate the impact of different observers on the accuracy of HGT on measuring bodyweights. Results: Mixed‐effects model results suggest HGT provides a relatively accurate estimation of weight (MAE: 2.66 kg) and relatively inaccurate estimation of DLWG (MAE 0.10 kg/d). Simulated data identified associations between time between weight dates and error in DLWG estimation, with MAE of individual DLWG estimation decreasing from 0.43 kg/d when 14 days apart to 0.08 kg/d when 70 days apart. Increased calf numbers reduced error rates of group DLWG estimation, with <0.05 kg/d error achieved in >90% of simulations when 12 calves were weighed 70 days apart. Conclusions: HGTs are relatively accurate at estimating individual bodyweights but are unreliable methods for measuring DLWG in individual calves, particularly weighed within a short‐time period. Estimates at group level however are relatively accurate, providing there is a suitable period of time between weigh dates and an appropriate number of calves per group.